Are Older People Aware of Potential Risks Related to Benzodiazepines They are Taking and Has Anything Changed in Risk Awareness Over Ten Years? - Celikkayalar Ercan; Airaksinen Marja; Kivelä Sirkka-Liisa; Nieminen Jenni; Kleme Jenni; Puustinen Juha (DOVE MEDICAL PRESS LTD, 2022)
Purpose: The use of benzodiazepines and related drugs (BZD) is common among older adults although there is growing evidence of their harmful effects. This study investigated how well older people are aware of the potential risks related to the BZD they are taking and whether the risk awareness has changed in the years between 2004 and 2015.Patients and Methods: The data were collected by interviewing BZD using home-dwelling patients aged >= 65 years with normal cognitive function (MMSE >= 20) who were admitted to the hospital within a 1 month study period in the years 2004 and 2015. Patients were asked whether they were aware of the ten main potential risks related to BZD use. A risk awareness score (range 0-10) was assessed for each patient, each known potential risk yielding one point.Results: The study included 37 patients in 2004 and 31 patients in 2015. In 2004,6/37 patients (16%), while 16/31 patients (52%) in 2015 had risk awareness scores between 6 and 10. Awareness of dependence (p=0.047), interaction with alcohol (p=0.001), dizziness (p=0.002) and developing tolerance (p=0.002) had improved, while awareness of the other potential risks remained unchanged, muscle weakness being the least known (3/37 in 2004 and 4/31 in 2015 were aware of it as a potential risk). Regular BZD use had declined (p=0.043) but pro re nata (PRN; when required) BZD use had increased (p=0.003) between the years 2004 and 2015.Conclusion: Older BZD users' awareness of some potential risks related to BZD use (dependence, interaction with alcohol, dizziness and developing tolerance) had improved between 2004 and 2015, while awareness of other potential risks remained unchanged.